2017
DOI: 10.1053/j.gastro.2017.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Inflammatory Diet Pattern and Risk of Colorectal Carcinoma Subtypes Classified by Immune Responses to Tumor

Abstract: Background & Aims Dietary patterns affect systemic and local intestinal inflammation, which have been linked to colorectal carcinogenesis. Chronic inflammation can interfere with the adaptive immune response. We investigated whether the association of a diet that promotes intestinal inflammation with risk of colorectal carcinoma was stronger for tumors with lower lymphocytic reactions than tumors with higher lymphocytic reactions. Methods We collected data from the molecular pathological epidemiology databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 69 publications
3
64
1
Order By: Relevance
“…A recent study demonstrated an association of pro-inflammatory diets such as red and processed meats, with a higher risk for CRC subtypes with absent/low-lymphocytic reaction than CRC subtypes with high-lymphocytic reaction in the tumor microenvironment. The pro-inflammatory diet-associated CRC subtype was enriched in MSS, CIMP-low/negative, and BRAF wild-type phenotype [ 112 ]. The expression level of CD274 in tumors is inversely associated with the density of FOXP3-positive regulatory T cells, revealing the potential interactions between the immune checkpoint pathway and the host immunity in colorectal carcinogenesis [ 113 ].…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…A recent study demonstrated an association of pro-inflammatory diets such as red and processed meats, with a higher risk for CRC subtypes with absent/low-lymphocytic reaction than CRC subtypes with high-lymphocytic reaction in the tumor microenvironment. The pro-inflammatory diet-associated CRC subtype was enriched in MSS, CIMP-low/negative, and BRAF wild-type phenotype [ 112 ]. The expression level of CD274 in tumors is inversely associated with the density of FOXP3-positive regulatory T cells, revealing the potential interactions between the immune checkpoint pathway and the host immunity in colorectal carcinogenesis [ 113 ].…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…Therefore, gene polymorphisms in the OCM pathway can decrease supplies of metabolites and cofactors, such as folate and B-vitamins, increasing the risk of CRC. Nutrients that can act as methyl donors related to these genes, including folate (vitamin B9) and vitamin B12, play integral roles in the phenotypic expression of related gene mutations in methylation pathways [ 28 , 29 , 30 , 31 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, when B. pseudocatenulatum (CECT 7765) was given orally to obese mice, it increased Tregs and reduced pro-inflammatory cytokines (IL-17A and TNF-a), which further supports the hypothesis that certain species may protect against chronic inflammation and development of CRC (51). In reports measuring dietary inflammatory factors (empirical dietary inflammatory pattern), individuals with higher inflammatory scores had fewer tumor-associated adaptive anti-tumor immune cells suggesting immune evasion (65). Moreover, using this same approach, higher inflammatory scores were associated with higher tumor-associated F. nucleatum in CRC (66).…”
Section: Discussionmentioning
confidence: 99%